Karonese Local Wisdom - seniman milala; indah arvianti (Universitas Aki, 2015)
Culture is the arts and other manifestations of human intellectual achievement regarded collectively, a refined understanding or appreciation, the customs, ideas, and social behaviour of a particular people or group. Besides, a culture actually contains local wisdom, that means the quality of being wise, the body of knowledge and experience that develops within a specified society or period. This journal focuses on parental and siblings relationship according to the culture and local wisdom in Karonese. It uses some theories to deal with culture, local wisdom and anthropolinguistics. The methods used to finish this research are method of data collection; collecting the data from Karonese local wisdom, (song, poetry, folklore, saying expression, wise word, proverbs, advise, slogans and traditional rituals and legends), method of padan which are language style, social elements, and implicit meaning, and informal method which explains the data descriptively. The research finds that there are many unique cultures and local wisdoms of Karonese in parental and sibling relationship represented in song, proverb, and folklore Keywords : culture, anthropolinguistics, local wisdom, Karonese